Low Cost Strategy for Micropropagation of Lilium Asiatic Hybrid Cv. Toscana - R Kaur (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2006)
A low cost protocol for in vitro propagation of Lilium cv. Toscana has been developed through incorporation of cost-effective media components. MS medium supplemented with 0.75 mg-1 BAP (6-benzylaminopurine) and 0.5 mg-1 NAA (α-naphthalene-acetic acid) was prepared with tapioca granules, table sugar and tap water in different combinations in place of agar-agar, sucrose and distilled water, respectively. Culture medium containing all the cost effective components was found to be the best for in vitro establishment of cultures yielding 6.00 bulblets per explant and medium supplemented with tapioca granules as cost effective component was found to be the best for in vitro multiplication of bulblets giving 3.70 bulblets per in vitro formed bulblet five weeks from third subculture. Tapioca supplemented MS medium containing 1 mg-1 NAA was significantly better than all the other modified media giving 86.62% in vitro rooting, 2.86 average root number and 4.60 cm average root length. For hardening of in vitro rooted bulblets, coco peat, peat moss and coco peat in combination with peat moss were found to be at par giving 100% survival.